Capability of P- and S-wave seismic refraction in delineating the Blang Bintang Sanitary Landfill (TPA) ground subsurface - Muhammad Syukri; Rosli Saad; Zul Fadhli (Songklanakarin Journal of Science and Technology (SJST), 2020)
The study was conducted at the Blang Bintang Sanitary Landfill in Aceh, Indonesia using P- and S-wave seismic refraction methods. The aim was to investigate the ground subsurface lithology. Arrival time against distance was plotted for Pand S-wave seismic refraction. Two ground subsurface boundaries were identified with three layers: top soil, highly weathered/weathered bedrock, and bedrock with Vp and Vs values of 480‒730 m/s and 256‒342 m/s, 1627‒2010 m/s and 525‒691 m/s, and 2500‒3588 m/s and 836‒840 m/s, respectively. The plots were also capable of indicating a fractured/fault zone with Vp and Vs values of 480‒730 m/s and 256‒691 m/s, respectively. Seismic refraction tomography of the P- and S-waves are capable of classifying the ground subsurface into four types of lithology: top soil, highly weathered bedrock, weathered bedrock, and bedrock with Vp and Vs values of <720 m/s and <450 m/s, 720‒1620 m/s and 450‒650 m/s, 1620‒2800 m/s and 650‒840 m/s, and >2800 m/s and >840 m/s, respectively. The fractured/fault and landfill zones were identified by seismic refraction tomography with Vp and Vs values of <720 m/s and <450 m/s, respectively. The seismic refraction of Vp and Vs have their own strengths because each of them considers different types of moduli and different velocity calculations.